Occupational therapy and rehabilitation: fostering mental resilience and professional re-entry - Smrity, Jarjina Akter; Mahbub, Kazi Abdus Satter; Afroze, Rushan; Nahar, Lutfur; Roy, Joyati (International Journal of Research in Medical Sciences, 2025)
Background: Occupational therapy (OT) plays a critical role in rehabilitation by addressing both physical and psychological challenges, fostering mental resilience, and supporting professional re-entry for individuals recovering from disabilities or illnesses. This study evaluated the impact of OT on mental resilience and professional re-entry among individuals undergoing rehabilitation at the Centre for the Rehabilitation of the Paralysed (CRP), Savar, Dhaka, Bangladesh. Methods: A cross-sectional study was conducted from August 2023 to July 2024, involving 150 participants recruited through purposive sampling. Standardized tools were used to assess mental resilience (resilience scale), employment readiness, self-efficacy, and satisfaction with OT services. Data were collected via structured questionnaires, interviews, and therapist records. Descriptive statistics summarized demographic data and therapy outcomes, while chi-square tests, paired t-tests, and logistic regression were used to analyse associations between OT interventions and mental resilience or professional re-entry. Results: The study observed a significant improvement in mental resilience, with 65% of participants transitioning to moderate or high resilience levels post-therapy. Employment readiness increased by 40%, with 55% successfully re-entering the workforce. Quality of life scores improved in 78% of participants, and 85% expressed satisfaction with OT services. Regression analysis identified mental resilience, self-efficacy, and social support as strong predictors of successful professional re-entry (p<0.05). Conclusions: OT interventions demonstrated a significant positive impact on mental resilience, quality of life, and employment outcomes. However, persistent barriers such as workplace accessibility and psychological challenges were noted. The findings underscore the need for integrated OT approaches to address these barriers and support holistic rehabilitation.